2012
DOI: 10.1515/hsz-2012-0157
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular aspartic protease SAP2 of Candida albicans yeast cleaves human kininogens and releases proinflammatory peptides, Met-Lys-bradykinin and des-Arg9-Met-Lys-bradykinin

Abstract: Bradykinin-related peptides, universal mediators of infl ammation collectively referred to as the kinins, are often produced in excessive amounts during microbial infections. We have recently shown that the yeast Candida albicans , the major fungal pathogen to humans, can exploit two mechanisms to enhance kinin levels at the sites of candidial infection, one depending on adsorption and activation of the endogenous kinin-generating system of the host on the fungal cell wall and the other relying on cleavage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…Bradykinin-related peptides, or kinins, are involved in nearly all types of inflammation and are clearly linked to pain phenotypes 10 . During inflammation, BDKRB1 and BDKRB2 expression is elevated and the local concentrations of their kinin agonists increase, although the precise concentrations of bradykinin at specific sites within the human body are largely unknown 56 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bradykinin-related peptides, or kinins, are involved in nearly all types of inflammation and are clearly linked to pain phenotypes 10 . During inflammation, BDKRB1 and BDKRB2 expression is elevated and the local concentrations of their kinin agonists increase, although the precise concentrations of bradykinin at specific sites within the human body are largely unknown 56 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, kinins induce the production of proinflammatory mediators, including nitric oxide, prostaglandins, and cytokines (e.g. IL-6) 10 , some of which are directly implicated in pain (e.g. PGE 2 and IL-6) 15–17, 19, 22, 23, 37, 45, 53, 61 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, blockade of ACE increases the bradykinin concentration, and it is known that the kinin system influences carcinogenesis by stimulating the growth, survival, and migration of cancer cells by altering the permeability of the blood tumor barrier and through the release of proinflammatory cytokines [35][36][37][38]. In addition, Fernandes et al [39], using a murine model of Ehrlich tumor, found that bradykinin antagonists may inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 99%